2020
DOI: 10.1155/2020/7917309
|View full text |Cite
|
Sign up to set email alerts
|

Osteokines and Bone Markers at Rest and following Plyometric Exercise in Pre- and Postmenopausal Women

Abstract: The effect of plyometric exercise on bone biomarkers has been studied in pediatric and young adult populations in order to better understand how exercise influences bone homeostasis. However, there are no such data in postmenopausal women, a group characterized by an uncoupling of the bone resorption-formation cycle. This study examined the serum concentrations of sclerostin, dickkopf-1 (DKK1), c-terminal crosslinking telopeptides of type I collagen (CTXI), and procollagen type I amino-terminal propeptide (PIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Preferably, both sexes should have been evaluated also in the elderly group, but we chose to prioritize men in an attempt to undermine the estrogen component related to aging. In the context of skeletal health, it could be argued that elderly women would be more relevant, although previous studies suggest that comparable results as in the present study can be expected ( 33 , 65 ).…”
Section: Study Strengths and Limitationssupporting
confidence: 66%
See 3 more Smart Citations
“…Preferably, both sexes should have been evaluated also in the elderly group, but we chose to prioritize men in an attempt to undermine the estrogen component related to aging. In the context of skeletal health, it could be argued that elderly women would be more relevant, although previous studies suggest that comparable results as in the present study can be expected ( 33 , 65 ).…”
Section: Study Strengths and Limitationssupporting
confidence: 66%
“…In continuation of this, a more recent study reported beneficial effects of plyometric exercise on the P1NP/CTX-1 ratio in premenopausal women, an effect that was blunted in postmenopausal women ( 33 ). The latter study reported the effect of BTMs as a formation/resorption ratio, using P1NP and CTX-1 ( 33 ). In the current study, we present P1NP/CTX-1 ratio, as part of a strategy to overcome the existing discrepancy between studies, as also suggested and used in several other reports ( 46 – 48 ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Sensitivity of the method for individual measurements was 6.225 ng/ml for PICP, with a coefficient of variation of 0–12%, for ICTP 6.5–7.2%. The results were interpreted by adopting the reference values of 30–300 ng/ml for PICP and 2.1–5.6 ug/l for ICTP [ 28 ].…”
Section: Methodsmentioning
confidence: 99%